Large-scale CO J = 1–0 observations of the giant molecular cloud associated with the infrared ring N35 with the Nobeyama 45 m telescope. (9th May 2018) - Torii, Kazufumi; Fujita, Shinji; Matsuo, Mitsuhiro; Nishimura, Atsushi; Kohno, Mikito; Kuriki, Mika; Tsuda, Yuya; Minamidani, Tetsuhiro; Umemoto, Tomofumi; Kuno, Nario; Hattori, Yusuke; Yoshiike, Satoshi; et al.
Abstract: We report an observational study of the giant molecular cloud (GMC) associated with the Galactic infrared ring-like structure N35 and two nearby H ii regions G024.392+00.072 (H ii region A) and G024.510−00.060 (H ii region B), using the new CO J  = 1–0 data obtained as a part of the FOREST Unbiased Galactic Plane Imaging survey with the Nobeyama 45 m telescope (FUGIN) project at a spatial resolution of 21″. Our CO data reveals that the GMC, with a total molecular mass of 2.1 × 10 6   M ⊙, has two velocity components of over ∼10–15 km s −1 . The majority of molecular gas in the GMC is included in the lower-velocity component (LVC) at ∼110–114 km s −1, while the higher-velocity components (HVCs) at ∼118–126 km s −1 consist of three smaller molecular clouds which are located near the three H ii regions. The LVC and HVCs show spatially complementary distributions along the line-of-sight, despite large velocity separations of ∼5–15 km s −1, and are connected in velocity by the CO emission with intermediate intensities. By comparing the observations with simulations, we discuss a scenario where collisions of the three HVCs with the LVC at velocities of ∼10–15 km s −1 can provide an interpretation of these two observational signatures. The intermediate-velocity features between the LVC and HVCs can be understood as broad bridge features, which indicate the turbulent motion of the gas at the collision interfaces, while the spatially complementary distributions represent the cavities created in the LVC by the HVCs through the collisions. Our model indicates that the three H ii regions were formed after the onset of the collisions, and it is therefore suggested that the high-mass star formation in the GMC was triggered by the collisions.